Molecular screening of transitional B cells as a prognostic marker of improved graft outcome and reduced rejection risk in kidney transplant - Perezpayá, Inés; Garcia, Sergio G.; Clos-Sansalvador, Marta; Sanroque-Muñoz, Marta; Font-Morón, Miriam; Rodríguez-Martínez, Paula; Vila-Santandreu, Anna; Bover, Jordi; Borràs, Francesc E.; Cañas, Laura; Franquesa, Marcella (Frontiers in Immunology, 2024)
Understanding immune cell dynamics in kidney transplantation may provide insight into the mechanisms of rejection and improve patient management. B cells have gained interest with a special relevance of the "regulatory" subsets and their graft outcome prognostic value. In this study, we aimed to prove that the direct immunophenotyping and target gene expression analysis of kidney transplant patients' fresh whole blood will help to identify graft rejection risk and assist in the monitoring of kidney transplanted patients. In this study, we employed flow cytometry and qPCR techniques to characterize B and T cell subsets within fresh whole blood samples, with particular emphasis on transitional B cells (TrB) identified as CD19 + CD24 hi CD38 hi . TrB are a relevant population in the context of kidney transplantation and are closely associated with regulatory B cells (Bregs) in humans. Patients were monitored, tracking pertinent clinical parameters and kidney-related events, including alterations in graft function and episodes of biopsy proven rejection. Higher percentages of TrB cells at 3 months after transplantation were positively associated with better graft outcomes and lower biopsy-proven acute rejection risk. Furthermore, a novel panel of B cell regulatory associated genes was validated at 3 months post-transplantation by qPCR analysis of peripheral blood mononuclear cell (PBMC) mRNA, showing high predictive power of graft events and prognostic value. These findings suggest that monitoring TrB may provide interesting patient management information, improve transplant outcomes, and allow for personalized drug regimens to minimize clinical complications.